Strengthening Multimodal Literacy through Digital Literary Text Learning: Enhancing Students’ Achievement in the Age of Disruption - Fradana, Ahmad Nurefendi; Suwarta, Nyoman; Sotlikova, Rimajon (Journal of Language and Literature Studies, 2025)
The rapid advancement of digital technology necessitates a transformative approach to literary education that extends beyond verbal literacy to embrace multimodal competencies (visual, auditory, interactive). This study aims to analyze the potential of digital literary texts as a medium for enhancing multimodal literacy amidst the challenges of the disruptive era, while identifying the enabling and constraining factors in its implementation within Indonesian educational contexts. Employing a descriptive qualitative approach, data were collected through case studies of literature instruction in three urban-based senior high schools, participatory observation of digital platforms (interactive e-books, literary webtoons, and short-story podcasts), and in-depth interviews with teachers and students. The analysis utilized Kress & van Leeuwen’s multimodal literacy theory and Paul Gilster’s digital pedagogy framework. Findings reveal that integrating multimodal elements—such as animated illustrations in poetry, hyperlinks in interactive narratives, and dramatic audio effects—significantly enhances students’ critical deconstruction of textual meanings and fosters learning motivation. However, disparities in digital infrastructure access and teachers’ limited technological proficiency emerge as primary barriers. The study recommends training programs for teachers in designing digital literature lessons using accessible tools (e.g., Canva, Book Creator) and fostering school-community partnerships with digital literacy initiatives. This research contributes to developing disruption-responsive literacy strategies and enriches Indonesian literary heritage through digital adaptation.